Prevalence and Drivers of Stalls and Reversals in Age at First Marriage in Sub-Saharan Africa - Ben Malinga John; Natalie Nitsche (Population Research and Policy Review, 2025)
The occurrence of stalls and reversals in age at first marriage despite ongoing education expansion is a salient and understudied demographic paradox of sub-Saharan Africa (SSA). Using Demographic Health Survey data, we contribute novel comprehensive evidence that illuminates this puzzle. First, we provide a systematic overview of stalls and reversals in age at first marriage among women born 1945–1999 in four broad SSA regions and 33 individual countries. Second, we test whether stalls and reversals in first marital age occurred because education expansion (a) dominated primary schooling, which is compatible with early marriages (compatibility hypothesis), or (b) led to changing socioeconomic conditions, which facilitated early marriages (diminishing returns hypothesis). We find that the median age at first marriage (MAFM) either stalled or reversed in 19 countries. At the regional level, MAFM stalled in Central and East Africa and reversed in Southern Africa. Stalls and reversals occurred primarily among the birth cohorts from 1965–69 through 1985–89. We find evidence for either hypothesis, yet mechanisms are context-dependent. We discuss the heterogeneity of education-marriage linkages across SSA and their implications on policies and programs aiming at eradicating early marriages in this region.
Keywords: 300; Union formation; Age at marriage; Female education; Sub-Saharan Africa